Comparative Law Analysis of Consumer Protection Law in E-Commerce Transaction Between Indonesia and United States - Felix Pratama Tjipto (UIR Law Review, 2021)
Innovation of technology and rapid growth of digitalization is steadily increasing its capacity in supporting human daily tasks, one of which is through online transactions that are increasing rapidly due to the occurrence of COVID-19 pandemic which forces people to do their activities from home. Nevertheless, the increased usage of technology directly affects the rise in creating loopholes and abuse of power which may violate the regulations and consumer’s rights in doing online transactions. This paper shall discuss and provide comparative and statute approach analysis between Indonesian and U.S law, its creation methods, organizations involved and law enforcement since it is important to address this issue in order to ensure that the enforcement of a solid legal framework is really being applied to regulate this matter.